Can I give food or drink to my terminally Ill child - Hasan, Taufiq Hidayat; Iqbal, Zahoor; Nasir, Ariffin; Nasir, Norsarwany; Taib, Fahisham (University Sains Malaysia, 2015)
Food is considered as a social responsibility of caregivers to their children. It has cultural connotation for all races notwithstanding their background and religious belief; that social responsibility should not be separated even in terminally ill patients. We recorded a case scenario of a terminally ill child who faced difficult end of life with inability to take oral fluids or food due to mechanical obstruction of duodenum by the pelvic rhabdomyosarcoma. From cultural context, the physical act of giving food and fluids to a sick person is considered “a display of one’s affection”. It is understandable that, once the dying phase has reached, and the body starts to shut down, administering fluids may not be useful despite it is deemed necessary from cultural point of view. This case illustrates an ethical dilemma in managing a child with end stage metastatic disease with multiple systemic complications, compounded with futility of medical care and complex social circumstances. It is quite challenging for physicians and relatives to provide good end of life care to patients in palliative care setting. Ensuring good quality of care, quality of life and quality of death are paramount to avoid suffering and distress among the patients and family members.